Rhizosphere Bacteria From Panax notoginseng Against Meloidogyne hapla by Rapid Colonization and Mediated Resistance - Wu, Wentao; Wang, Jingjing; Wang, Zhuhua; Guo, Liwei; Zhu, Shusheng; Zhu, Youyong; Wang, Yang; He, Xiahong (Frontiers in Microbiology, 2022)
Root-knot nematodes (RKNs) are soil-borne pathogens that severely affect Panax notoginseng growth and productivity. Thus, there is an urgent need for biological control agents or green nematicides to control root-knot nematodes. Rhizosphere bacteria can effectively control RKNs through different mechanisms. In this study, the three rhizosphere Bacillus strains, isolated from the root of P. notoginseng, were evaluated for the nematicidal activity and biological control efficacy against root-knot nematodes. In addition, we also evaluated the colonization ability of the two bacterial strains with significant biocontrol effect and dynamic regulation of genes related to systemic resistance in P. notoginseng. The rhizosphere Bacillus velezensis GJ-7 and Bacillus cereus NS-2 showed high nematicidal activity against Meloidogyne hapla in vitro and significantly reduced the number of root galls in three different control experiments. The results of colonization experiments showed that the strains GJ-7 and NS-2 colonized P. notoginseng root rapidly and stably. Additionally, the colonization of the strains NS-2 and GJ-7 activated the defense-responsive genes in P. notoginseng. These results indicated that the B. cereus strain NS-2 and B. velezensis strain GJ-7 have the potential for successful ecological niche occupation and enhance plant resistance and therefore could be considered as potential biocontrol agents against root-knot nematodes.